2011
DOI: 10.1038/hdy.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA effects on fitness in Drosophila subobscura

Abstract: We tested different fitness components on a series of conspecific mtDNA haplotypes, detected by RFLPs in Drosophila subobscura. Additionally, haplotype VIII, endemic to the Canary Islands, was tested upon its own native nuclear DNA background and upon that of the rest of mtDNAs tested herein. We found that both nuclear and mitochondrial DNA can have a significant effect upon their hosts' fitness, and that negative selection is one of the mechanisms that can intervene in this species' mtDNA haplotype pattern. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Drosophila subobscura represents a very interesting model system for microevolutionary studies of mtDNA variation, both because of the extensive data sets on mtDNA variability collected in nature and because of the interesting pattern of mtDNA haplotype polymorphism (see ). It is, however, premature to even try to associate phenotypic effects with particular mtDNA sequence variants: less than a handful of haplotypes have been studied in terms of their phenotypic effects and the mtDNA genome has only been partially sequenced (Beckenbach et al ., ; Moya et al ., ; Stenico & Nigro, ; Brehm et al ., ; Christie et al ., ; Castro et al ., ; Christie et al ., ; Herrig et al ., ). Although these efforts have revealed variation at a very large number of both synonymous and nonsynonymous sites in several genes, it is unclear which genetic variants are associated with phenotypic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila subobscura represents a very interesting model system for microevolutionary studies of mtDNA variation, both because of the extensive data sets on mtDNA variability collected in nature and because of the interesting pattern of mtDNA haplotype polymorphism (see ). It is, however, premature to even try to associate phenotypic effects with particular mtDNA sequence variants: less than a handful of haplotypes have been studied in terms of their phenotypic effects and the mtDNA genome has only been partially sequenced (Beckenbach et al ., ; Moya et al ., ; Stenico & Nigro, ; Brehm et al ., ; Christie et al ., ; Castro et al ., ; Christie et al ., ; Herrig et al ., ). Although these efforts have revealed variation at a very large number of both synonymous and nonsynonymous sites in several genes, it is unclear which genetic variants are associated with phenotypic effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous laboratory experiments have suggested that flies carrying the two dominant haplotypes show differences in some life‐history traits and in behaviour (Castro et al ., ; Christie et al ., ). However, these studies did not control for nuclear genetic background and, when expressed in the same uniform nuclear background, phenotypic differences between mtDNA haplotypes seem much less pronounced (Christie et al ., ). This implies that mitonuclear epistasis may be important in D. subobscura , and other studies have provided evidence supporting the existence of mitonuclear epistatic interactions between mtDNA and nuclear markers (Fos et al ., ; García‐Martinez et al ., ; Castro et al ., ) which is further supported by within‐population linkage disequilibrium between mtDNA haplotypes and nuclear genetic markers (Oliver et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These strong fitness benefits were not uniform across all nuclear backgrounds and in some cases had a striking negative effect (e.g., C 4 nuclear background with mtDNA from E 1 ), indicating that mt-n epistasis can overwhelm even strong mt haplotype effects. While independent effects of Drosophila mitotypes are frequently noted (Christie et al 2011;Pichaud et al 2012Pichaud et al , 2013, experiments designed to examine multiple mitotypes in different nuclear backgrounds have found that mt-n epistasis is a more important predictor of phenotype (Dowling et al 2007b;Montooth et al 2010). The impact of mt-n epistasis may explain why fitness effects associated with human mt haplotypes are often difficult to replicate.…”
Section: Intraspecific Mt-n Epistasismentioning
confidence: 99%
“…Interestingly, haplotypes with low frequencies in the New Zealand population had a significantly lower output of new queens than more common haplotypes, although they were similar in the production of worker cells. Rare haplotypes with reduced relative fitness have also been observed in fruit flies and bumble bees (Christie et al, ; Christie, Picornell, Moya, Ramon, & Castro, ; Johnson et al, ) and purifying selection likely leads to the observed low frequencies of the deleterious haplotypes (Flight et al, ; Montooth, Meiklejohn, Abt, & Rand, ). Analysis of >11,910 bp of rare and common mitochondrial haplotype sequences among the New Zealand population found no nonsynonymous mutations that would indicate an obvious reason for dysfunction causing the low reproductive output of these rare haplotypes.…”
Section: Discussionmentioning
confidence: 96%